Finanzas Personales para Mujeres: Una Visión Desde el Concepto de Independencia Financiera, Empoderamiento Económico y Autonomía Económica (2023)
The power of personal finance for women, where every decision traces the path to financial freedom, demonstrating that women are taking control of their economic decisions. From breaking deep-rooted stereotypes to outlining firm strategies, the aim is to carry out a documentary compilation that allows understanding the interrelation between the concepts, advantages and benefits of financial independence, economic empowerment and economic autonomy, knowing its direct impact on women's personal finances.